Metopelloides paguri sp. nov., a new species of symbiotic stenothoid amphipod (Crustacea: Amphipoda: Stenothoidae) associated with sublittoral hermit crabs from the Russian coasts of the Sea of Japan - Marin, Ivan; Sinelnikov, Sergey (Zootaxa, 2012)
A new species of amphipod from the genus Metopelloides Gurjanova, 1938 (Crustacea: Amphipoda: Stenothoidae) asso-ciated with two species of sublittoral hermit crab species, Pagurus pectinatus (Stimpson, 1858) and Elassochirus cavi-manus (Miers, 1879) (Crustacea: Decapoda: Paguridae), is described from the Russian coasts of the Sea of Japan. The newspecies clearly differs from the congeners by the combination of morphological features such as telson without lateralspines, an elongated mandibular palp with single apical setae, the structures of distoventral palmar margins of subchelaon gnathopods I and II in females, bright white-red body coloration. Thus, the record of Metopelloides paguri sp. nov.represents the second record of the family Stenothoidae in the association with sublittoral hermit crabs from the Sea of Japan.